Kontribusi Pendidikan Dalam Membangun Pengetahuan dan Karakter Bangsa - Benawa, Arcadius (Bina Nusantara University, 2012)
Education principally is process of making young people into maturity level in facing many aspects of life, especially in education, skills, and behaviour. Threfore, education is supposed to give positive contributions for the development of knowledge and nation building. On the other hand, nowadays people were concerned on the fact that even tough the education was well-developed in Indonesia, but this development did not reflect to the , in which they were not able to perform their self image as educated and having positive characters nation. Article wanted to answer that problems, that was to find out annapproriate education system that was able to give contribution on the development of the knowledge and characters’ of the nation.